Dynamic response of transiently trapped entanglements in polymer networks - Agudelo Mora, Diana Carolina (2014)
The structure and viscoelastic response of polymer networks are highly sensitive to the presence of pendant chains. These imperfections, that are unavoidable produced during a cross-linking reaction, reduce the cross-linking density and affect the damping response of elastomers. In this work the dynamics of pendant chains present in a cross-linked network is investigated using end-linked poly(dimethyl-siloxane) networks with well defined structure. For this purpose, model networks containing 10 and 20 wt% of two different monodisperse pendant chains with molecular weights well above the critical entanglement molecular weight and some of their blends were prepared. It was found that, within this range of concentration of pendant chains, the long-time dynamic response of the networks was nearly insensitive to the content of pendant material but deeply influenced by the average molar mass of these defects. While the equilibrium behavior of the networks can be well described by a mean field theory for rubber elasticity, the long time relaxational dynamics can be rationalized in terms of the Pearson-Helfand picture for the arm retraction process. Within this theoretical picture, the dynamics can be explained in terms of the molecular architecture of the network, the Rouse time and the weight average molar mass of the pendant material.